Germline HNPCC gene variants have little influence on the risk for sporadic colorectal cancer. Issue 1 (January 1997) - Tomlinson, I P; Beck, N E; Homfray, T; Harocopos, C J; Bodmer, W F
Abstract : Hereditary non-polyposis colorectal cancer (HNPCC) is a syndrome of inherited bowel and other cancers that has been said to account for up to 15% of all colorectal carcinomas (CRCs). HNPCC can now be diagnosed at the molecular level by detecting germline mutations in genes involved in mismatch repair. A current problem is to determine the prevalence of HNPCC mutations in colon cancer patients with limited or no family history, especially in cases of early onset. We have identified 50 cases of non-polyposis colorectal cancer without a family history of CRC or any other HNPCC cancer, who presented under the age of 45 years. Germline HNPCC variants (at the hMSH2 or hMLH1 loci) were detected in a small minority of cases (6%). The variants that we have found may be new or low penetrance mutations, or even polymorphisms. It remains possible that some of our sample have an inherited predisposition to CRC that is not caused by HNPCC mutations or by known polyposis syndromes. Our data suggest that most HNPCC mutations occur in families and have high or moderate penetrance. New or low penetrance HNPCC mutations probably do not contribute significantly to the risk of colorectal cancer in the general population and probably account for much fewer than 15% of all CRCs. Our results question whether mass population genetic screening programmes are worthwhile for diseases such as HNPCC using current technology.